Recognition of Fast Electromagnetic Transients in HV Overhead Lines - Gudzius, S.; Morkvenas, A.; Markevicius, L. A.; Miliune, R.; Markevicius, L. (Elektronika ir Elektrotechnika, 2011)
This article is about recognition of fast electromagnetic transients in HV overhead lines. The modeling of the very fast electromagnetic transients in HV overhead lines is important and rather complicated task especially when the goal deals with a problem of the recognition of the fast electromagnetic transients in the electric power network. Precise modeling of the fast electromagnetic transients in the overhead distribution lines helps to define more precise processes characteristics, and create more accurate recognition models. The paper describes the results of the modeling of the fast electromagnetic transients in HV overhead power lines and discusses the ways of its application for the recognition of the fast electromagnetic transients.